Case Report: The Effect of Murottal Therapy of Surah Ar-Rahman on the Stability of Vital Signs in Infants with Severe Asphyxia - Falasifah Ani Yuniarti; Athaya Intan Fitriani; Yetty Purnamaningsih (International Journal Of Health Science, 2025)
Neonatal asphyxia is a critical condition and one of the leading causes of neonatal mortality, especially in developing countries such as Indonesia. This condition is marked by impaired oxygen exchange, leading to hypoxemia, hypercapnia, and metabolic acidosis. Prompt and appropriate management is essential, including the use of non-pharmacological interventions such as Qur’anic murottal therapy. Surah Ar-Rahman is often chosen for its soft and soothing rhythm, which is believed to have a calming physiological effect on infants. This study used a case study design with an interventional approach involving one infant diagnosed with severe asphyxia treated in the NICU of RSUD Tjitrowardoyo Purworejo. The intervention involved playing a recitation of Surah Ar-Rahman for 15–30 minutes daily over five consecutive days. Vital signs monitored included oxygen saturation, heart rate, respiratory rate, and body temperature. Results showed an increase in oxygen saturation from 87% to 100%, a decrease in heart rate from an average of 137 to 127.4 bpm, a reduction in respiratory rate from 53.6 to 44.8 breaths/minute, and a slight temperature decrease from 37.36°C to 37.3°C. These findings suggest that Qur’anic murottal therapy, particularly Surah Ar-Rahman, can contribute to the stabilization of vital signs in neonates with severe asphyxia. This therapy may serve as a supportive intervention in neonatal nursing care and is recommended for use both in clinical settings and at home.